Innovation audit of a consumer electronics multi-national corporation - Lee, Kok Fah. (2008)
This dissertation aims to find out the innovativeness of a Consumer Electronics Multi-National Corporation. An Integrative Model of Innovation in Organizations and a survey instrument developed to validate data collection from the organization; had been proposed by Mr. H. K. Tang. To achieve this aim, agreement was obtained from the company's top management on the proposed audit. Ten departments were selected for this audit. Seven were product development departments and the rest were support departments.